FORMULASI DAN UJI ORGANOLEPTIK SABUN PADAT BERBASIS MINYAK NABATI, MINYAK JELANTAH DAN ECOENZIM - Adriyani, Lies Wuryanita; Rizki, Nuzulul Anggi; Khairunisa (Yayasan Nusantara Hasana Berdikari, 2025)
The improper management of used cooking oil poses risks of environmental pollution and adverse health impacts. On the other hand, eco-enzyme has recently gained attention as a natural additive in environmentally friendly products. This study aimed to formulate solid soap using vegetable oils, used cooking oil, and eco-enzyme, as well as to evaluate its pH and organoleptic properties. Three soap formulations were prepared using NaOH as the base: Formula A (used cooking oil), Formula B (vegetable oils), and Formula C (vegetable oils with eco-enzyme). The required amount of NaOH was calculated using SoapCalc to ensure a balanced saponification reaction. The soaps were produced using the cold process method and cured for one month prior to testing. Organoleptic evaluation was conducted by panelists based on color, aroma, texture, foam, and skin feel, while pH was measured using Universal Test Paper. The results showed that Formula A (used cooking oil) retained a distinctive odor, but was still acceptable to panelists with an average organoleptic score of 3.2 (neutral) and a pH of 10. Formula B (palm, coconut, and olive oils) was favored in terms of appearance, aroma, texture, foam, and skin sensation, with an average score of 4.0 and a pH of 8. The addition of eco-enzyme in Formula C produced a fresher aroma and was the most preferred by panelists, achieving the highest average score of 4.2, with a pH of 7. All three formulations met the pH requirements of SNI 3532:2021. These findings indicate that SoapCalc is effective in designing balanced formulations, while the utilization of used cooking oil and eco-enzyme shows potential in producing environmentally friendly solid soaps.